THE EFFECTIVENESS OF TEACHER’S STRATEGIES FOR TEACHING READING TO NEWS ITEM TEXT - Emma Fashikhatur Rohmadania (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2021)
Anecdotal evidence shows that some teachers are still using traditional teaching strategies. Because of the use of traditional teaching strategies, the students feel bored to learn in the class. As stated by Johnson (2008) “A simple behaviorist principle is that if we find something to be enjoyable in learning based on teacher’s strategies, we are more likely to do that thing again. If we find something to be boring, frustrating, or meaningless in learning based on teacher’s strategies, we are less likely to do that thing again.” (p.12). Therefore, if the teacher’s strategies make the students feel bored, the teacher cannot be labelled as an effective teacher. This also applies in teaching reading. In this thesis, the researcher seeks to investigate what strategies were employed a teacher at an Islamic state school. In addition, the effectiveness of the use of the strategies for teaching reading skill in news item text was also examined. In other words, the current study aims to explore how the teacher’s strategies on students’ reading skill in news item text were employed in effective ways. This study used a mixed-methods research design, in which data were obtained from two types of data collection methods, i.e. interview and questionnaire. The data were qualitative and quantitative. The researcher found that the teacher used several strategies for teaching reading to news item text; those are reading aloud, reading comprehension, and small-group discussion. The students reported that these strategies were effective for them to learn the reading skill in news item texts.